2008
DOI: 10.4049/jimmunol.180.7.4476
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Uptake Is Limiting in T Cell Activation and Requires CD28-Mediated Akt-Dependent and Independent Pathways

Abstract: T cell activation potently stimulates cellular metabolism to support the elevated energetic and biosynthetic demands of growth, proliferation, and effector function. We show that glucose uptake is limiting in T cell activation and that CD28 costimulation is required to allow maximal glucose uptake following TCR stimulation by up-regulating expression and promoting the cell surface trafficking of the glucose transporter Glut1. Regulation of T cell glucose uptake and Glut1 was critical, as low glucose prevented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
782
2
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 716 publications
(811 citation statements)
references
References 47 publications
19
782
2
8
Order By: Relevance
“…Because facilitated metabolism is coupled to consumption of large amounts of intracellular materials such as amino acids and glucose, T cells must boost the rate of uptake of those nutrients by setting up special devices such as effective organic solute transporters. Supporting this notion, the glucose transporter 1 is upregulated upon activation of T cells (4)(5)(6). T cells also must enhance amino acid uptake rate to support increased protein synthesis accompanied by cytokine production and cell proliferation during activation.…”
mentioning
confidence: 81%
“…Because facilitated metabolism is coupled to consumption of large amounts of intracellular materials such as amino acids and glucose, T cells must boost the rate of uptake of those nutrients by setting up special devices such as effective organic solute transporters. Supporting this notion, the glucose transporter 1 is upregulated upon activation of T cells (4)(5)(6). T cells also must enhance amino acid uptake rate to support increased protein synthesis accompanied by cytokine production and cell proliferation during activation.…”
mentioning
confidence: 81%
“…In response to activation, T cells exhibit a remarkable metabolic shift from fatty acid oxidation to glycolysis (50)(51)(52). Thus, increased sugar metabolism may lead to higher levels of UDP-GlcNAc, which would promote OGT activity.…”
Section: T Cell Activation Leads To Regulation Of Ogt Localization Anmentioning
confidence: 99%
“…C57BL/6 mice were obtained from Jackson Laboratories, and Glut1 transgenic and ERRα −/− mice were previously described (2,24). Mice were housed and cared for at Duke University under an Institutional Animal Care and Use Committee approved protocol.…”
Section: Methodsmentioning
confidence: 99%
“…These processes require energy expenditure and biosynthesis (2,3) and T-cell stimulation triggers a rapid increase in cellular metabolism to support activation and differentiation pathways (4,5). We have shown that specific metabolic demands differ between CD4 + T-cell subsets, as Teff cells (Th1, Th2, and Th17) are dependent upon glycolysis, while Tregs use and require lipid oxidation (6).…”
mentioning
confidence: 99%